"The Latino Community is Not Accustomed to Arguing for the Rights of Their Children": How Latina Mothers Navigate Special Education. Issue 2 (15th March 2023) - Mortier, Kathleen; Arias, Edith
ABSTRACT: With a rapidly increasing number of Latinx students in a special education system that requires parent advocacy, it is imperative to study the perspectives Latinx families have on how to improve family-school partnerships. In this research, semi-structured interviews with 10 Latinx mothers who have children with disabilities led to insights about stressors and barriers, how families can be empowered, and how trusting partnerships can be facilitated. Implications for the field of special education are discussed.